General studies, information and communication technology and contemporary mission in Africa - Ibenwa, Christopher N.; Ambrose, Ihenacho; Uroko, Favour C. (Hervormde teologiese studies, 2024)
This study examines the relationship between general studies, information and communication technology (ICT), and contemporary evangelism in Nigeria. Information and communication technology (is defined as a diverse set of technological tools and resources used to transmit, store, create, share or exchange information. These technological tools and resources include computers, the Internet (websites, blogs and emails), live broadcasting technologies (radio, television and webcasting), recorded broadcasting technologies (podcasting, audio and video players, and storage devices) and telephony (fixed or mobile, satellite, visio/video conferencing, etc.). Contemporary evangelism and mission in Africa is a radical approach embarked upon by agents of modern religious thoughts and practices to expand the horizons of the mission of religion to mankind in the present dispensation through general studies (GS) and ICT programmes. Through the medium of ICT, Christian evangelism has received a boost in television, radio broadcasts, computers, and the Internet across cities and nations. This work is an attempt to examine the methods adopted by early missionaries in evangelising Africa vis-à-vis the modern techniques of GS and ICT, the challenges of mission, the concept of ICT and its various forms such as phones, television, radio, computers, and the Internet, and their relevance to mission. This work therefore adopted historical, missiological, and phenomenological approaches in the analysis of data.ContributionThis work discovers that radical development in communication across the globe has influenced and affected Christian methods and practices of carrying out ‘the mission of religion’ and its evangelical perspective, among others.